2015
DOI: 10.1123/smej.2014-0013
|View full text |Cite
|
Sign up to set email alerts
|

Social Media as a Learning Tool: Sport Management Faculty Perceptions of Digital Pedagogies

Abstract: This research explored the use of social media within the sport management discipline in a North American context, specifically investigating how sport management academicians use social media as a teaching and learning tool. An online survey garnered the social media literacies of sport management faculty (N = 132). Compared with cross-discipline studies that have measured similar interests, sport management faculty appear to have a limited awareness of social media applications. Only 61% of study participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 0 publications
0
17
0
1
Order By: Relevance
“…O'Boyle (2014) discussed the opportunity for faculty to use social media in the classroom to engage students through a familiar communication medium. Lebel et al (2015) suggested using social media and other digital pedagogies to connect with students in the face-to-face setting but expressed concern that utilizing said techniques in an online course may be difficult due to the absence of eye-to-eye contact.…”
Section: Faculty Perceptions Of Online Educationmentioning
confidence: 99%
“…O'Boyle (2014) discussed the opportunity for faculty to use social media in the classroom to engage students through a familiar communication medium. Lebel et al (2015) suggested using social media and other digital pedagogies to connect with students in the face-to-face setting but expressed concern that utilizing said techniques in an online course may be difficult due to the absence of eye-to-eye contact.…”
Section: Faculty Perceptions Of Online Educationmentioning
confidence: 99%
“…Today's technology allows young adults to engage with the world through social media outlets making it almost mandatory for college professors to be engaging themselves. The use of social media in an online course is unique in that it enables students to engage in discussions about real world issues related to course content outside of the online classroom setting (Lebel et al, 2015). Social media provides a unique tool for faculty to engage their students both within and outside the classroom.…”
Section: Student Perceptions Of Online Educationmentioning
confidence: 99%
“…Edwards and Finger (2007) discussed the possibility of implementing hyper-pedagogy techniques (i.e., virtual reality and the use of gaming) into a sport management classroom. Students engage with technology and expect faculty to engage with technology through course management websites, email, and other forms of digital communications (Lebel, Danylchuk, & Millar, 2015;Proserpio & Gioia, 2007).…”
Section: Student Perceptions Of Online Educationmentioning
confidence: 99%
“…Descriptive statistics were primarily used to examine trends related to social media implementation, as well as faculty proficiency and usage rates. The researchers also utilized one-way ANOVA with Bonferroni post hoc and t tests in order to examine group differences across sport management faculty (Lebel, Danylchuk, & Millar, 2015). The results of this particular study indicated that just 61% of study participants had previously incorporated social media into their course design; however, a majority of faculty agreed that social media could provide positive enhancement to teaching and learning (Lebel, Danylchuk, & Millar, 2015).…”
Section: Experiential Learning In Sport Management Academiamentioning
confidence: 98%
“…Another study that helps inform the current study is Lebel, Danylchuk, and Millar's (2015) study that measured faculty perceptions of social media as a learning tool across sport management programs. Much like the present study, their study focused on a specific pedagogical approach (social media), and then sought out to investigate both the use of social media across sport management programs, and more specifically, how sport management faculty use social media as a teaching and learning tool (Lebel, Danylchuk, & Millar, 2015). The following research questions guided their study:…”
Section: Experiential Learning In Sport Management Academiamentioning
confidence: 99%